CLIL in Action: Voices from the Classroom - Marsh, David; Cañado, María Luisa Pérez; Padilla, Juan Ráez (Cambridge Scholars Publishing, 2015)
This volume explores the current position of CLIL on the three main fronts where it is attracting particular attention in specialized literature, namely, implementation, research, and teacher training. To this end, it presents evidence from national and international research projects, governmentally-financed pedagogical initiatives, grassroots experiences and investigations, and inter-institutional training programs which offer insights into how CLIL is working in action on the afore-mentioned three levels. The opening section of the book ("CLIL in action: Practical considerations") provides a window into how CLIL implementation is unravelling at the grassroots level vis-á-vis key aspects for CLIL development, such as the design of materials, the use of ICT, and the importance of extramural exposure. The second part ("The effects of CLIL on language learning: Research-based evidence") explores some key areas for future research, showcasing how engaging in research as a device that drives reflection is the best possible way to continue moving the CLIL agenda forward. Finally, in the third part ("Preparing teachers for CLIL: Practical proposals"), the interface of research and pedagogy is discussed, as the former informs the latter in a clear instantiation of what Coyle (2011) terms "evidence-based practice" in setting necessary teacher training actions in place. As such, the volume addresses three burning issues in the CLIL scenario through practical and research-based proposals of tried-and-true CLIL development. If all three strands - implementation, research, and training - dovetail and progress in harmony, a solid template will be built for the future and the CLIL agenda will be pushed forward. By pooling together the insights of a set of researchers, teacher trainers, policy makers, and grassroots practitioners, this volume will contribute to this much-needed endeavour.